GLOBALISASI BAHASA INGGRIS: SO WHAT? - I. Gusti Astika (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2015)
The process of globalization and the role of English have been widely recognized as two inseparable entities which have influenced all aspects of our lives including education.  The responses to globalization and the role English in academic community have been variable which may have considerable impacts to the quality of educational human resources. In academic community, the quality human resources have become the key competitive advantage of many universities. With the advancement of science and technology, the role of English has been gaining more prominence since new knowledge and information in science and technology are to a large extent packaged in English. This awareness should bring about a different paradigm of educational management and a modified teaching methodology which accommodate the use of technology, in particular the use of the internet. This is an exciting challenge to the university management to design a program for teachers and students which aims to develop the necessary knowledge and skills in English in order to acquire knowledge and keep informed and updated with the latest information and technology. Within the area of English language teaching, this can be realized through the design of ESP (English for Specific Purposes) or EOP (English for Occupational Purposes) based on needs analysis to identify target tasks in the specialized fields of study and design pedagogical activities for classroom implementation.